DOI: 10.11606/t.8.2011.tde-23052012-162304
|View full text |Cite
|
Sign up to set email alerts
|

Trajetórias educacionais dos jovens residentes num distrito com elevada vulnerabilidade juvenil

Abstract: Resumo BITTAR, Mariana. Trajetórias educacionais dos jovens residentes num distrito com elevada vulnerabilidade juvenil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…We know from qualitative studies that participating in the dynamics of criminal factions represents a very strong risk factor predicting homicide, even stronger than gender, age and colour/race 7 . Initially, we thought that one variable that may work as a proxy to hone in on the profile of these precarious and criminalised workers would be the level of schooling, as different studies have already shown that young offenders have a substantial lack of schooling (BITTAR, 2012). Unfortunately, however, data on the education of homicide victims was ignored in almost 32% of the homicides recorded in DataSUS for the four cities between 2000 and 2019, while the variable "race" was only ignored in 3.4% of the recorded homicides.…”
Section: Conceptual and Methodological Clarificationsmentioning
confidence: 99%
“…We know from qualitative studies that participating in the dynamics of criminal factions represents a very strong risk factor predicting homicide, even stronger than gender, age and colour/race 7 . Initially, we thought that one variable that may work as a proxy to hone in on the profile of these precarious and criminalised workers would be the level of schooling, as different studies have already shown that young offenders have a substantial lack of schooling (BITTAR, 2012). Unfortunately, however, data on the education of homicide victims was ignored in almost 32% of the homicides recorded in DataSUS for the four cities between 2000 and 2019, while the variable "race" was only ignored in 3.4% of the recorded homicides.…”
Section: Conceptual and Methodological Clarificationsmentioning
confidence: 99%
“…Sabemos pelos estudos qualitativos que o fato participar das dinâmicas faccionais é um enorme preditor de homicídios, ainda mais forte do que gênero, idade e cor/raça 7 . Inicialmente, pensamos que uma variável que poderia funcionar como um proxy para aproximarmo-nos do perfil desses trabalhadores precarizados e criminalizados seria o nível de escolaridade, porque diferentes estudos já demonstraram que os jovens autores de infrações têm alta defasagem escolar (BITTAR, 2012). Infelizmente, no entanto, os dados sobre a escolaridade das vítimas de homicídio foram ignorados em quase 32% dos homicídios registrados no DataSUS para as quatro cidades, entre 2000 e 2019, enquanto a variável "raça" só foi ignorada em 3,4% dos homicídios registrados.…”
Section: Precisões Conceituais E Metodológicasunclassified
“…Isto é uma constatação em pesquisas (SCHWARTZMAN; CASTRO, 1991;SILVA, 2003;SETTON, 2005;PIOTTO, 2016, BITTAR, 2011, mostram que a realidade de uma grande parcela dos jovens-alunos da escola pública que saem do Ensino Médio e poucos ingressam na universidade, muitos já constituíram famílias outros tem que abandonar os estudos para poder trabalhar e cuidar da família. Assim, é a realidade de muitos jovens da periferia.…”
Section: __ Se Eles Vão Entrar Numa Universidade Particular Ou Pública Ainda Não Sei Mas Têm Muitos Chegando Na Universidade Pública Issounclassified